พัฒนาต้นแบบชุดกรองเซรามิกเมมเบรนสำหรับการกรองน้ำสกัดเสริมสุขภาพจากเปลือกมังคุด - ดรุณี ผ่องสุวรรณ (มหาวิทยาลัยสงขลานครินทร์, 2022)
L.plantarum DW12 was used as a starter culture to produce manerage.There were 4 sets of experiments as follows:Set A,a tradition.mangosteen peel, cane sugar and potable water (w.w:v = 3:1:10) without starter culture.Set B is set A with 5% starter culture and 0.5% monosodium glutamate (MSG). Set C is atraditional formula flesh mangosteen, cane sugar and potable water (3 :1 : 10) withoutstarter culture and set D is set C with 5% starter culture and 0.5% monosodium glutamate(MSG). Initial total bacterial counts (TBC) in all sets were between 5.11 and 5.62 logCFU/ml. At the end of fermentation (12 weeks), TBC in set A, B, C and D were 4.17, 4.14,4.18 and 2.84 log CFU/ml, respectively, while initial lactic acid bacteria (LAB) were 2.33,5.2, 4.9 and 5.16 log CFU/mI, respectively, and at the end of fermentation the LAB levelswere 2.60. 4.14, 2.43 and 3.26 log CFU/ml, respectively. The initial number of yeasts in allsets was approximately 5 log CFU/ml and at the end of fermentation set C had thehighest number of 4.13 log CFU/ml.The final concentration of sugar in all sets at week 12was in a range of 0.02-0.51%, pH 3.2-3.8, electrical conductivity of 916-3308 HS/cm withtotal acidity of 0.46-0.95%, Moreover, mangosteen beverage fermentation had antioxidantactivity and the maximum antioxidant activity found at week 12 in all sets. Based on DPPHand total phenolic content, set B produced the highest antioxidant activity followed byset A C and D, respectively. Bacterial indicators were not found in all sets including totalcoliforms, Escherichia coli and pathogens; Salmonella sp., S. aureus and Clostridiumperfringens. Antibacterial activity was found in all sets against the growth of testedbacteria mentionedpreviously.Tubular-type ceramic membranes made from alumina were prepared by slip castingmethod. The tube dimensions are 22 and 34 mm outer diameter, 220 mm in length and 3mm thickness (surface area = 0.01 and 0.02 m'). After sintering at temperature of 1100cthe ceramic membrane possessed an average porosity of 47-49 % with pore diameter of0.3-1 micron.Filtration unit was designed to install 3-4 ceramic tubes (total surface area = 0.05and 0.07 m') with cross-flow pattern and made of PVC pipe with 0.1 m internal surfacearea. Tests showed the pure water permeate at 137.80 kpa is between100 and 168 LhrThe permeate of fermentedmangosteen beverage set B and C was reduced to 1.37 andunit was designed to install 3-4 ceramic tubes (total surfaced 0.07 m²) with cross-flow pattern and made of PVC pipe with 0.1 m²internal surfacearea. Tests showed the pure water permeate at 137.80 kPa is between100 and 168 Lhr-1The permeate of fermentedmangosteen beverage set B and C was reduced to 1:37 and2.55 Lhr-1at 34.45-137.80 kPa, respectively. Results showed that the laboratory-madeceramic filter can reduced numbers of yeast, TBE and LAB tde< 1.47 log CFU/ml,respectively. Ethanols in all sets after filtration were still 2.02, 4.27, 4.45 and 5.61 %,respectively. The total sugar, pH, total acidity, including antioxidants activity before andafter filtrations were slightly different. The filtered broth can inhibited all 4 testedbacteria, no detection of bacterial indicators and foodborne pathogens was found. Resultsnsory test using Hedonic test found that all sets after filtration in theacceptance than before filtration due to their more clearness.